DESAIN MEDIA INTERAKTIF NUSAEXPLORE BERBASIS ARTICULATE STORYLINE UNTUK MENINGKATKAN LITERASI BUDAYA (SISWA KELAS V SDN GAPRANG 01 KABUPATEN BLITAR) - Isnawaitus Sa'adah; Shofi Nur Amalia; Cindya Alfi (Jurnal Pendidikan Sosial Keberagaman, 2026)
Cultural literacy is a crucial skill that elementary school students need to develop in order to understand, appreciate, and preserve the cultural diversity of Indonesia. However, the topic of “The Cultural Diversity of Indonesia” in Pancasila Education is often taught using learning media that provide limited student engagement, resulting in low interest, boredom, and difficulties in understanding cultural content. This study aimed to develop Nusaexplore, an interactive learning media based on Articulate Storyline, evaluate its validity and feasibility, and measure the improvement of students’ cultural literacy after its implementation. This study employed a Research and Development (R&D) approach using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The participants were fifth-grade students of SDN Gaprang 01, Blitar Regency. Data were collected through observations, interviews, questionnaires, and tests. The findings indicated that Nusaexplore achieved validation scores of 94% from the material expert and 98% from the media expert, both categorized as “highly valid.” Teacher evaluations showed a feasibility score of 92%, indicating that the media was “highly feasible” for classroom use. Students’ cultural literacy demonstrated a significant improvement, as reflected by an average N-Gain score of 0.8928 (89.28%), which falls into the high category and indicates the effectiveness of the learning media. Previous studies have also supported these findings, showing that interactive learning media based on Articulate Storyline can enhance student engagement and improve understanding of learning materials. Therefore, the Nusaexplore media developed in this study can be considered valid, feasible, and effective in supporting the improvement of cultural literacy among fifth-grade elementary school students. Keywords: Nusaexplore, Articulate Storyline, Cultural Literacy.